Analisis Yuridis Peradilan Akibat Salah Tangkap dalam Tindak Pidana Narkotika: Judicial Analysis of the Effects of Wrongful Arrest in Narcotics Crimes - Yosua Yosua (Jurnal Hukum Bisnis, 2026)
Arrests without proper procedure violate human rights and pose a problem in the criminal justice system. These violations can include procedural and administrative errors, violations of the suspect's rights, and the use of false witnesses or evidence. Criminal law aims to protect the public from crime while ensuring that no innocent person becomes a victim of law enforcement errors. Therefore, arrests must be carried out in accordance with applicable legal provisions. This study examines two main issues: the pretrial process for victims of wrongful arrest in narcotics crimes and the forms of compensation that victims can receive. Legal protection for victims of wrongful arrest is regulated in Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), which provides the right to compensation and rehabilitation. The amount of compensation is further regulated by Government Regulation Number 92 of 2015, an amendment to Government Regulation Number 27 of 1983. The study was conducted through a legal review of relevant laws and regulations. The results of the study indicate that victims of wrongful arrest can file claims for compensation and rehabilitation through the pretrial mechanism as stipulated in Article 77. Article 95 of the Criminal Procedure Code. The need for rehabilitation and compensation generally arises from errors by law enforcement officials, both during the investigation and prosecution stages. These errors can include incorrectly naming suspects or indictments based solely on the Investigation Report without adequate verification. Therefore, compensation and rehabilitation mechanisms are important instruments for achieving legal justice for victims of wrongful arrest.